The culture play, a key role in management consulting firms - Costa, R. L.; Pereira, L.; Dias, Á.; Gonçalves, R. (International Journal of Productivity and Quality Management, 2022)
Organisational culture assumes a fundamental part of the life of every organisation. The development of human resources management and its increasingly strategic role have shown the importance of organisational culture and its effects on multiple aspects of organisations. With the complexity and competitivity associated with the rapid changes of todays labour market, such importance becomes more determinant to the success of organisations. Therefore, the present article aims to understand the main factors that influence the organisational culture of management consulting firms and to develop an adequate model for such companies. This article is based on data from 15 interviews and 107 questionnaires responded by consultants with a variety of ages, positions, seniorities, from management consulting organisations, operating in Portugal, with several different intervention areas and that offer different types of consulting. The results and conclusions comprise information concerning the main factors behind the organisational culture in management consulting firms.